Hydrogen bonding investigation of poly(3-hydroxybutyrate) / glycol chitosan blends studied by infrared and terahertz spectroscopies - Marlina, Dian; Sato, Harumi (Advance Sustainable Science, Engineering and Technology, 2019)
Poly(3-hydroxybutyrate) (PHB)/glycol chitosan (GC) polymer blend was developed as one of the new biopolymer materials. Effects of different PHB / GC concentrations were analysed as a function of the blend compositions by using Fourier transform infrared (FTIR) and terahertz (THz) spectroscopies to investigate the changes in the higher-order structure and bonding of hydrogen. The higher-order structure and hydrogen bonding monitored in this study include the crystalline structure and (C=Oâ€¦H-C) hydrogen bonding of PHB. The FTIR and THz spectra showed that PHB's higher-order structure transforms into the less-order structure by adding GC without altering the crystalline structure and PHB's intramolecular (C = O ... H-C) hydrogen bonding with increasing GC concentration. Because of the addition of GC, the intensity ratio of THz bands figure out the crystalline dynamics of PHB, the helical structure deformation occurs first followed by the weakening of intramolecular (C = O ... H-C) hydrogen bonding within PHB-PHB molecules.Â Keywords: Chitosan, higher-order structure, hydrogen bonding, low-frequency vibrational spectroscopy